2014
DOI: 10.7314/apjcp.2014.15.13.5355
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Sonography and Hysteroscopy in the Detection of Premalignant and Malignant Polyps in Women Presenting with Postmenopausal Bleeding and Thickened Endometrium

Abstract: Background: To assess the role of sonographic endometrial thickness and hysteroscopic polyp size in predicting premalignant and malignant polyps in postmenopausal women. Materials and Methods: A total of 328 postmenopausal women with abnormal uterine bleeding and thickened endometrium underwent operative hysteroscopy due to detection of endometrial polyps were included in this retrospective study. Preoperative endometrial thickness measured by transvaginal ultrasonography and polyp size on hysteroscopy were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…Güner et al found an endometrial thickness average of 22.7 mm for endometrial cancer and did not encounter malignant endometrial pathologies in subjects with endometrial thickness < 8 mm [10]. Another study found that endometrial thickness determined by transvaginal ultrasonography has 92.3% sensitivity and 95% specificity for endometrial cancer detection in cases with endometrial thickness ≥ 19.50 mm [13]. In our study, we found that endometrial thickness increased in malignant endometrial pathologies, and we did not encounter endometrial carcinoma in cases where the endometrial thickness was < 7 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Güner et al found an endometrial thickness average of 22.7 mm for endometrial cancer and did not encounter malignant endometrial pathologies in subjects with endometrial thickness < 8 mm [10]. Another study found that endometrial thickness determined by transvaginal ultrasonography has 92.3% sensitivity and 95% specificity for endometrial cancer detection in cases with endometrial thickness ≥ 19.50 mm [13]. In our study, we found that endometrial thickness increased in malignant endometrial pathologies, and we did not encounter endometrial carcinoma in cases where the endometrial thickness was < 7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, ≤ 4 mm endometrial thickness has a negative predictive value of 99% for endometrial cancer [6][7][8]. Above 4 mm endometrial thickness is a nonspecific finding and may be associated with endometrial polyp, submucous myomas or endometrial hyperplasia [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An optimal cut-off of 5 mm is being proposed (418) and our data clearly exceeds this limit. Hysteroscopy also aids the diagnosis, allowing visual confirmation and endometrial biopsy during the procedure, evidently increasing the screening sensitivity (781018). For patients without PMB, the 5 mm cut-off could be recommended as described from previous studies (418).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to evaluate the cause of PMB because of its association with gynecologic malignancies (23456). Early diagnosis may help improve survival rates, hence several diagnostic tools such as transvaginal ultrasonography or hysteroscopy have been implemented for early and accurate detection of malignancy (1478910). Recently, cancer prevalence rates have been changing due to better cancer screening modalities and health insurance coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The need for hysteroscopic assessment of endometrium is being emphasized more and more in evidence based medicine. 7 8 9 10 11 …”
Section: Discussionmentioning
confidence: 99%